Employees’ attitudes towards female managers in terms of job satisfaction - Özbeyli, Deniz (My University, 1999)
This is a research work on measuring the attitudes of employees towards female managers in terms of job satisfaction. It is a fact that both males and females can be seen as managers in every field of work life. It has been recognized that female managers are facing problems like gender discrimination, stereotypical attitudes, glass ceilings, not only in Turkey but all around the world. Female managers who are suffering from the dilemma of professional career and family life should also cope with those problems, as well. This study has attempted to reach a conclusion on measuring the attitude of employees towards, specifically, female managers. Following the literature review a questionnaire has been designed, for pilot study, it has been applied to 30 employees in various work places. After the development of the questionnaire, 282 employees in Finance, Production, Education, Service and Health sectors have been selected. The criteria in the selection of the employees was that they should be working under female managers. The demographic variables in the questionnaire have been as age, sex, marital status, educational level, sector, experience and social security systems. The findings of the research have shown that there are significant differences between the employees in the age group of 18-24 and 30-34 in terms of satisfaction with manager. The youngest participants of the research have taken the highest mean scores expressing better attitudes. Females and singles have taken the highest mean scores. There was a significant difference between single and married employees, singles expressing more favorable attitudes. There is a highly significant difference between the finance sector and, production and education sectors in terms of satisfaction levels. Employees in finance sector tend to have more positive attitudes. Experience has been found inversely proportional to the satisfaction mean scores. The satisfaction levels of the employees working less than 1 year is significantly higher than those working more than 10 years. Finally, it was found that there was a significant difference between SSK and Bağ-Kur members, SSK members with higher satisfaction levels.

Bu tez çalışanların, iş tatmini açısından, kadın yöneticilere karşı tutumlarını ölçen bir araştırmadır. Hem kadınların hem de erkeklerin çalışma hayatının her alanında yönetici olarak görülebildiği bir gerçektir. Kadın yöneticilerin, cinsiyet ayrımı, kalıplaşmış yargılar, cam tavan gibi problemlerle sadece Türkiye'de değil tüm dünyada karşılaşmakta olduğu farkedilmiştir. Mesleki kariyer ve aile hayatı arasında ikilemde bulunan kadın yöneticilerin ayrıca bu problemlerle de başa çıkması gerekmektedir. Bu araştırma, çalışanların özellikle kadın yöneticilere karşı tutumlarını ölçmede bir sonuca varmaya çalışmaktadır. Yazın incelemesinden sonra bir anket oluşturulmuş ve pilot çalışma için farklı işyerlerinden 30 kişiye uygulanmıştır. Anket geliştirildikten sonra, finans, üretim, eğitim, hizmet ve sağlık sektörlerinden seçilen 282 kişiye uygulanmıştır. Bu kişilerin seçimindeki temel ölçüt hepsinin kadın yöneticiler altında çalışıyor olmalarıydı. Anketteki demografik değişkenler olarak, yaş, cinsiyet, medeni hal, eğitim düzeyi, sektör, tecrübe ve sosyal güvenlik sistemi belirlenmiştir. Araştırmanın sonucunda 18-24 yaş grubu ve 30-34 yaş grubu arasında yöneticiden tatmin olma açısından anlamlı fark bulunmuştur. Ankete katılan en genç kitle daha iyi tuıtum sergilemektedir. Kadınlar ve bekarlar en yüksek otalama puanı almışlardır. Bekar ve evlilerin tutumları arasında anlamlı fark bulunmuştur. Bekarlar daha iyi bir tutum geliştirmişlerdir. Finans sektörüyle üretim ve eğitim sektörleri arasında yöneticiden tatmin olma düzeyi açısından anlamlı bir fark bulunmuştur. Finans sektöründekiler daha olumlu tutumlar gösterme eğilimindedirler. 1 yıldan daha az çalışanların tatmin olma düzeyi 10 yıldan fazla süredir çalışanlarınkinden daha yüksektir. Son olarak SSK'lıların yöneticiden tatmin olma düzeyi Bağ-Kur'lularınkinden anlamlı derecede daha yüksektir.
Keywords: İŞ TATMİNİ